ROLE AND PLACE OF MEDIATION IN THE LEGAL TRADITION OF THE PEOPLE OF KAZAKHSTAN - Ayupova, Z. K.; Kussainov, D. U.; Nagan, Winston (Scientific Journal of Pedagogy and Economics, 2018)
A legal conflict occupies certain position among different conflicts in the society. A conflict is considered as legal, if there are certain signs as an object, object, subject, and also motivation, sides conduct the definite dispute;usually, the conflict has some legal consequences. Dispute, for instance, is necessary to examine as the objectively expressed contradiction of wills of two sides, that consists of carrying legal character of requirements of one side, resisting to the legal requirement of the second side, that hampers the real satisfaction of this requirement. Under legal status the actual position of person is understood as the legal in accordance with that application of compulsion in regard to the approval of public organs subject. From the origin of dispute about the right ofits subjects the personal interest appears in the permission. A legal conflict has the constituents, such as an object and subject of conflict. To our mind, the sides of the conflict arethe physical persons, foreigners, persons without citizenship; state, public organizations, possessing legal personality come forward the subjects of conflict. On the basis of legal personality there is cooperationbetween each other in the process of conflict